Dari Ritual “Yasin 41” ke Marketing Politik pada Pemilukada: Studi Kasus Majelis Zikir Thuthma’ilnalqulub (MZT) - Hidayat, Ziaulhaq; Ramadhan, Muhammad (Jurnal Review Politik, 2017)
This article describes the involvement of Majelis Zikir Tathma’innulqulub (MZT) in the local leaders election. Although this particular case occurred in the Medan city, it’s also explain in general the majlis dhikr phenomenon in Indonesia’s political practice. This phenomenon is interesting since the involvement of majlis dhikr is uncommon in the political world—as commonly known, sufism possess different (spiritual) orientation. The involvement can be best described as a political brand of sufism: in ritual and practice in supporting one of the local candidate. Thus, it describes the ritual of “yasinan and dhikr” from the beginning of election until the end as a “political ritual”. In addition, MZT also serves as a political marketing—spiritual adviser as well as political consultant; while in the practical aspect, MZT involved in hidden and public campaign. However, the candidate supported by MZT was lost. This fact explains that political brand of sufism has no significant influence in politics practice.